2022
DOI: 10.3390/met12081388
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Grain Refinement Effects of Zr on Mg Alloys: A Review

Abstract: As the lightest structural materials, Mg alloys show great effectiveness at energy saving and emission reduction when applied in the automotive and aerospace fields. In particular, Zr-bearing Mg alloys (non-Al containing) exhibit high strengths and elevated-temperature usage values. Zr is the most powerful grain refiner, and it provides fine grain sizes, uniformities in microstructural and mechanical properties and processing formability for Mg alloys. Due to the importance of Zr alloying, this review paper sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Second, the widely accepted theory for grain refinement during solidification for various alloys is still the inoculation effect, e.g. Ti with B in Al [52], Zr in Mg, or Al [53]. This mechanism seems impossible for hypoeutectic Ti-B alloys when β-phase grains are solidified before the eutectic-originated TiB phase [54].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the widely accepted theory for grain refinement during solidification for various alloys is still the inoculation effect, e.g. Ti with B in Al [52], Zr in Mg, or Al [53]. This mechanism seems impossible for hypoeutectic Ti-B alloys when β-phase grains are solidified before the eutectic-originated TiB phase [54].…”
Section: Discussionmentioning
confidence: 99%
“…A segregation effect is the most pronounced at the minor content of alloying element or impurity and the distribution of the elements became more homogeneous at its high content [ 16 ]. Second, the widely accepted theory for grain refinement during solidification for various alloys is still the inoculation effect, e.g., Ti with B in Al [ 48 ], Zr in Mg, or Al [ 49 ]. This mechanism seems impossible for hypoeutectic Ti-B alloys when β -phase grains are solidified before the eutectic-originated TiB phase [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [11] reported the latest progress on the effect of Zr in the grain refinement of magnesium alloys. The Mg-Zr master alloy ensured a clean interface between the Zr particles and Mg solution, which was beneficial to the diffusion of Zr elements and improved the utilization rate of nucleation.…”
Section: Contributionsmentioning
confidence: 99%